2014
DOI: 10.1186/cc13701
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation in adult patients with hematologic malignancies and severe acute respiratory failure

Abstract: IntroductionAcute respiratory failure (ARF) is the main reason for intensive care unit (ICU) admissions in patients with hematologic malignancies (HMs). We report the first series of adult patients with ARF and HMs treated with extracorporeal membrane oxygenation (ECMO).MethodsThis is a retrospective cohort study of 14 patients with HMs (aggressive non-Hodgkin lymphoma (NHL) n = 5; highly aggressive NHL, that is acute lymphoblastic leukemia or Burkitt lymphoma, n = 5; Hodgkin lymphoma, n = 2; acute myeloid leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 33 publications
3
102
1
Order By: Relevance
“…Benefits of extracorporeal membrane oxygenation in immunocompromised patients remain uncertain, although an increasing body of evidence suggests feasibility in selected cases. Following a case series suggesting feasibility and some long-term survival in adult patients with haematological malignancies [11], Smith et al reported similar results in nine paediatric critically ill neutropenic patients, the majority of whom had high-grade haematological malignancies [12]. In this setting, hospital mortality was found to be as high as 44% with long-term survival of 22% [12].…”
Section: Treatmentssupporting
confidence: 49%
“…Benefits of extracorporeal membrane oxygenation in immunocompromised patients remain uncertain, although an increasing body of evidence suggests feasibility in selected cases. Following a case series suggesting feasibility and some long-term survival in adult patients with haematological malignancies [11], Smith et al reported similar results in nine paediatric critically ill neutropenic patients, the majority of whom had high-grade haematological malignancies [12]. In this setting, hospital mortality was found to be as high as 44% with long-term survival of 22% [12].…”
Section: Treatmentssupporting
confidence: 49%
“…With improvements in ECMO technology and expertise lowering morbidity and mortality, the criteria for the use of ECMO may be extended to ARDS patients with hematological malignancies such as acute leukemia and lymphoma (7,12). Wohlfarth et al (7) reported a remarkable 50% survival rate, despite the presence of numerous factors known to be associated with an adverse outcome in patients with hematological malignancies undergoing ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…Wohlfarth et al (7) reported a remarkable 50% survival rate, despite the presence of numerous factors known to be associated with an adverse outcome in patients with hematological malignancies undergoing ECMO.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations